45. COMPLIANCE WITH TREATMENT OF PATIENTS WITH HYPERTENSION AT THE CARDIOVASCULAR CLINIC OF BAI CHAY HOSPITAL QUANG NINH IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current status of treatment adherence of hypertensive patients at the Cardiology Clinic, Bai Chay Quang Ninh Hospital in 2024 and some related factors.Method: Cross-sectional descriptive study with analysis.Results: The rate of compliance with hypertension treatment of the study subjects from the average level or higher is 55,0%, the poor level is 45,0%. The results of the analysis to find the relationship show that factors such as: Diet, smoking, drinking alcohol, home monitoring of hypertension, periodic re-examination, duration of illness and complications are related to treatment adherence with p
Keywords: Treatment adherence; Hypertension; Bai Chay Hospital